The Comorbidities and it Impact on the outcome of COVID-19 Patients - Al-Janabi, Alaa Hussein Khudhair (South Asian Journal of Social Sciences and Humanities, 2023)
Background: The existence of associated diseases presents a major clinical challenge in the approach and management of COVID-19 patients. Objectives: To study the effect of common comorbidities on the severity, outcome, and duration of hospital stay among confirmed COVID 19 cases. Methods: Descriptive cross-sectional study. A 2574 conditions were involved in the current study. All the PCR confirmed cases in 2 COVID-19 centers at Babylon province/Iraq were included for the period from March till September 2020. A constructed questionnaire used as a method of data collection which including socio-demographic data, clinical presentation of the infection and its severity, associated comorbidities that the patient may suffer from and the duration of hospital stay and outcome. Results: the study shown that the mean of age 48.7 (±16.4) years, Diabetes Mellitus was the most prevalent associated comorbidity (25.0%), then hypertension with a prevalence of (23.4%), (84.0%) of the patients who had comorbidities had severe/critical illness compared to (54.1%) for patients who are free from comorbid illnesses with significant P value of (0.001), case-mortality ratio was 26.4% among patients with comorbidities compared to 10.6% among the patients free from comorbidity (P<0.001). Conclusions: associated diseases had significant impact on the severity of the duration and outcome of COVID-19 infection, patients with comorbidities must have additional preventive measures and they should be at the beginning in receiving the COVID-19 vaccine to prevent the deteriorations and bad consequences.